MENSAHABATI KAUM LGBT DAN REMAJA NAKAL SEBAGAI SALAH SATU BENTUK PENGABDIAN KEPADA MASYARAKAT - Sri Wahyuni; Yohanis Kotte; Nastiti Puspita Rini (STT Ebenhaezer Tanjung Enim, 2022)
The objectives of the Community Service program are: (1) providing a correct understanding of LGBT; (2) factors that influence juvenile delinquency; (3) teenagers are able to maintain holiness their lives; (4) able to understand about transitional times; (5) parents, educators and God 's servants can guide them; (6) have methods in ministry to youth. This is done based on the struggles and problems faced by parents, church and community. The solutions to overcome these problems are as follows; (1) providing regular assistance in anticipating the occurrence of LGBT practices; (2) instilling spiritual values through spiritual guidance; (3) the government 's role in protecting the indicated Indonesian citizens and facilitating their guidance; (4) the government is able to uphold the values and norms of Pancasila based on the 1945 Constitution. The method used in this programme is by; (1) gaining information from the students; (2) pre-field: (3) interview; (4) team preparation; (5) implementation; (6) Evaluation and follow-up. The results found are; (1) knowing about LGBT and changing the level of phases in their lives and daring to say no to LGBT; (2) training youth's faith to continue to be faithful to the Lord Jesus; (3) being able to become blessings in the environment where they are; (4) become Christian youth who are dedicated and have high integrity.